Diabetes Diminishes the Portal-Systemic Collateral Vascular Response to Vasopressin via Vasopressin Receptor and Gα Proteins Regulations in Cirrhotic Rats - Lee, Jing-Yi (Public Library of Science, 2013)
Liver cirrhosis may lead to portal-systemic collateral formation and bleeding. The hemostatic effect is influenced by the response of collateral vessels to vasoconstrictors. Diabetes and glucose also influence vasoresponsiveness, but their net effect on collaterals remains unexplored. This study investigated the impact of diabetes or glucose application on portal-systemic collateral vasoresponsiveness to arginine vasopressin (AVP) in cirrhosis. Spraque-Dawley rats with bile duct ligation (BDL)-induced cirrhosis received vehicle (citrate buffer) or streptozotocin (diabetic, BDL/STZ). The in situ collateral perfusion was done after hemodynamic measurements: Both were perfused with Krebs solution, D-glucose, or D-glucose and NaF, with additional OPC-31260 for the BDL/STZ group. Splenorenal shunt vasopressin receptors and Gα proteins mRNA expressions were evaluated. The survival rate of cirrhotic rats was decreased by STZ injection. The collateral perfusion pressure changes to AVP were lower in STZ-injected groups, which were reversed by OPC-31260 (a V2R antagonist) and overcome by NaF (a G protein activator). The splenorenal shunt V2R mRNA expression was increased while Gα proteins mRNA expressions were decreased in BDL/STZ rats compared to BDL rats. The Gαq and Gα11 mRNA expressions also correlated with the maximal perfusion pressure changes to AVP. Diabetes diminished the portal-systemic collateral vascular response to AVP in rats with BDL-induced cirrhosis, probably via V2 receptor up-regulation and Gα proteins down-regulation.